FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGELOLAAN LIMBAH CAIR TERHADAP PASAR IKAN DI PONDOK BARU KECAMATAN BANDAR KABUPATEN BENER MERIAH - Afrina, Ade; Alamsyah, Sanjaya; HS, Nurlaely (Akper Kesdam I/Bukit Barisan Padang, 2025)
ABSTRACTWaste treatment is an effort to reduce or stabilize pollutants so that when disposed of they do not harm the environment and health.The purpose of this study is to Determine Factors Related to Liquid Waste Management to the Fish Market in Pondok Baru, Bandar District, Bener Meriah Regency in 2024. The design of this study uses Descriptive Analytics with a cross-sectional design of the study. The sample taken was 32 respondents. The sampling technique uses the Total sampling technique, which is sampling the entire population. This research has been conducted at the Pondok Baru Impres Market, Bandar District, Bener Meriah Regency. on October 22-23, 2024. Based on the results of statistical analysis using the Chi Squer test, the Relationship between Traders' Knowledge and Liquid Waste Management to the Fish Market was obtained with a P value = 0.002 < 0.05. There is a relationship between the attitude of fish traders and Liquid Waste Management towards the Fish Market with a P value = 0.000 < 0.05. There is a Relationship between Facilities and Infrastructure with Liquid Waste Management to the Fish Market with a significant value of 0.014< 0.05 and there is no relationship between the level of education and liquid waste management to the Fish Market with a value of 0.603 >0.05. Fish traders at the Pondok Baru Market are expected to improve knowledge and attitudes as well as improve infrastructure to be able to manage liquid waste in the fish market. Keywords : Knowledge, Attitude, Infrastructure, Fish Liquid Waste Management